Способи викладу принципів права у нормативно-правових актах - Юхимюк, О.; Iukhymiuk, O. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті здійснено теоретичний аналіз способів, прийомів юридичної техніки, спрямованих на формулювання принципів права в національному законодавстві. Обгрунтовано висновок, згідно із яким принципи права визнаються основою правової системи. Вони формулюються в нормативно-правових актах у вигляді політичних гасел, сприяють формулюванню правової оцінки певного явища, можуть бути закріплені у формі чіткої директиви, містити терміни оціночного характеру чи формулу справедливості. Окремою групою є принципи, обмежені винятками, та принципи, що обмежують сферу дії норм права. In modern Ukraine girect regulative influence of principles of law on public relations is growing. Often principles of the law confessed at international and regional level become the part of national legislation both by ratification or implementation and by the way of exposition in the articles of normative-legal acts. A question of fixing of principles of law in national normative-legal acts, and also adequate interpretation and realization of principles of law acquire the special actuality nowadays. Principles of law are formulated in normative-legal acts as political slogans, they assist the formulation of legal estimation of the certain phenomenon, can be envisaged in form of a clear directive, contain the categories of evaluation character or formula of justice. A separate group are the principles limited to the exceptions, that limit the sphere of action of norms of law, and principles from that the exceptions are not envisaged, however their formulation has character of exceptions as they limit the sphere of application of general norms which are not considered principles of law.
Methods of Exposition of Principles of Law in Normative-legal Acts.
Keywords: принципи права; правова система; нормативно-правовий акт; оціночні поняття; principles of law; legal system; normative-legal act; evaluation concepts